Nutrient Digestibility, Nitrogen Metabolism and Rumen Fermentation Patterns of West African dwarf Rams fed diets containing graded levels of Garcinia kola ( Bitter kola) Seed Meal - Jinadu, K. B.; Akingbade, A. O.; Adekanbi, A. O.; Olona, J. F.; Adekunjo, R. K.; Saka, A. A.; Agboola, T. B.; Olagbaju, O. T.; Olufayo, O. O. (Nigerian Journal of Animal Science, 2023)
Garcinia kola contains secondary metabolites which can be used to modulate rumen ecology to improve its feed degradability and microbial efficiency. Therefore, this study was conducted for 84 days to assess the nutrient digestibility, nitrogen metabolism and rumen fermentation patterns of West African dwarf (WAD) sheep fed diets containing graded levels of Garcinia kola seed meal (GKSM). Sixteen WAD rams weighing 12.00±0.05kg were randomly allotted to four dietary treatments containing 0%, 2.5%, 5% and 7.5% of GKSM in a completely randomized design. Data obtained on digestibility, nitrogen metabolism and Rumen fluid were analyzed using one way analysis of variance. Results obtained showed that crude protein digestibility (91.63%), Nitrogen Free Extract (17.85%) and Ash digestibility (91.08%) were significantly (p <0.05) highest in Ram fed diet 3. Rams on diet 2 and 3 were similar (p>0.05) but significantly (p <0.05) higher in crude fibre digestibility than those on diets 1 and 4. Nitrogen intake values decreased across the dietary treatments as the GKSM inclusion levels increased. Total volatile acids values obtained were significantly highest in Ram fed diet 3 when compared with other dietary treatments. It was concluded that rams fed diets containing 5% GKSM had better Nitrogen metabolism and nutrient digestibility.